1978
DOI: 10.21236/ada064689
|View full text |Cite
|
Sign up to set email alerts
|

Instructional Systems Development (ISD) in Air Force Flying Training.

Abstract: 20 3. 4. 1 Imp lementation Factors 20~. 4. 2 O r g a n i z a t i o n a l F a c t o r s 27 3. 4. 3 Management Factors 32 3. 4. 4 I'er s on ne l , R e s o u r c e s , and Facilities. 43 3. 4. S R e l a t i o n s h ip to Other Agencies! Activities 4 CONCLUSION 4. 1 Scope of ISD 4. 2 Status of ISD 4. 3 State of ISD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…While these arguments have merit, years of experience have demonstrated that in most task domainsparticularly those that have a rather well defined problem and solution space -a well conducted behavioral analysis will lead to effective and efficient teaching and testing. Indeed, one could argue that even today, the majority of problems in the training environment can be traced to an inadequate task analysis in behavioral terms (e.g., Miller et al, 1978;Gibbons, 1980). However, the question remains of what should be done in those task domains that are too dynamic and/or complex to lend themselves to an unambiguous definition of conditions and criteria.…”
Section: Conclusion For Task Analysismentioning
confidence: 99%
“…While these arguments have merit, years of experience have demonstrated that in most task domainsparticularly those that have a rather well defined problem and solution space -a well conducted behavioral analysis will lead to effective and efficient teaching and testing. Indeed, one could argue that even today, the majority of problems in the training environment can be traced to an inadequate task analysis in behavioral terms (e.g., Miller et al, 1978;Gibbons, 1980). However, the question remains of what should be done in those task domains that are too dynamic and/or complex to lend themselves to an unambiguous definition of conditions and criteria.…”
Section: Conclusion For Task Analysismentioning
confidence: 99%